High-toughness aluminum-titanium-aluminum alloy and preparation method thereof

By using a combination technology of titanium hydride powder and modified carbon fiber, combined with vacuum hot press sintering and vacuum suspension smelting, the problems of low density and high cost of titanium aluminum alloy are solved, and the preparation of high toughness aluminum-titanium aluminum alloy is achieved, with excellent mechanical properties and high density.

CN119710499APending Publication Date: 2025-03-28CHIZHOU JIUHUA MINGKUN ALUMINUM IND
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411917160.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The prior art is difficult to effectively reduce the low density of titanium-aluminum alloys, improve their high temperature resistance, toughness and heat resistance, and have high production costs, and the finished product has defects in shrinkage and looseness.

Method used

Titanium hydride powder is used instead of pure titanium powder, and aluminum-titanium-aluminum alloy is prepared by vacuum hot press sintering and vacuum suspension smelting. Modified carbon fibers are added to promote in-situ self-generating reaction to form second-phase ceramic particles, refine grain size and improve strength and toughness.

Benefits of technology

It significantly improves the strength and toughness of aluminum-titanium-aluminum alloy, reduces the oxygen content, forms a fine and uniform pore structure, improves the density and creep resistance of the material, and is simple in process and can be prepared in batches.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005207083290000131
    Figure BDA0005207083290000131
  • Figure BDA0005207083290000141
    Figure BDA0005207083290000141
Patent Text Reader

Abstract

The invention belongs to the technical field of metallurgical preparation, and provides a high-toughness aluminum-titanium-aluminum alloy and a preparation method thereof.The preparation method comprises the following steps that 1, all raw materials are weighed by weight, aluminum powder, titanium hydride powder and yttrium hydride powder are mixed, and mixed powder is obtained; 2, the mixed powder obtained in the step 1 is subjected to vacuum hot pressing sintering and cooling, and an aluminum-titanium-aluminum alloy master batch is obtained; step 3, mixing the aluminum-titanium-aluminum alloy master batch obtained in the step 2 with modified carbon fibers, and carrying out vacuum suspension smelting to obtain a composite molten liquid; and 4, the composite molten liquid obtained in the step 3 is subjected to investment casting and cooling, and the titanium-aluminum alloy is obtained. According to the preparation method of the high-toughness aluminum-titanium-aluminum alloy, operation is easy, raw materials are easy to obtain, large-scale production is easy to achieve, and the prepared titanium-aluminum alloy is stable in chemical component and good in processing property and has the advantages of being high in density, good in creep resistance, high-temperature strength, oxidation resistance and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metallurgical preparation, and specifically relates to a high-toughness aluminum-titanium-aluminum alloy and a preparation method thereof. Background Art

[0002] With the replacement of aviation power units, the internal ambient temperature of aerospace engines has gradually increased. The currently mature nickel-based alloys can no longer meet the high-temperature working requirements. Titanium-aluminum alloys can replace nickel-based alloys as lightweight and high-strength structural parts in the fields of aerospace, automobiles, and precision manufacturing due to their excellent high-temperature and corrosion resistance. Titanium-aluminum-based intermetallic compounds have regular atomic arrangements, strong metal bonds and covalent bonds, and have the advantages of light weight, high-temperature oxidation resistance, and good creep resistance. They can be used as raw materials for high-temperature and corrosion-resistant special coatings to cope with various harsh conditions of use.

[0003] The main preparation methods of traditional high-density titanium aluminum alloys include ingot metallurgy and powder metallurgy. Among them, the ingot metallurgy method has high requirements for smelting equipment, a long smelting process, and requires repeated smelting to eliminate the problem of alloy element segregation. The material utilization rate is low (less than 60%), and due to its poor thermal conductivity, it is impossible to use this process to manufacture large-sized titanium aluminum alloy ingots, resulting in extremely high manufacturing costs for titanium aluminum alloys prepared by this method. Although the powder metallurgy method can better solve the problems of alloy element segregation and low material utilization, its process is still relatively long at present. Generally, titanium powder and aluminum powder need to be synthesized into titanium aluminum alloy powder first, and then the preparation of titanium aluminum alloy is realized by powder metallurgy process, and the price is still relatively expensive. At the same time, due to the large difference in density and melting point of titanium and aluminum, it is very difficult to prepare titanium aluminum alloys with uniform composition. The titanium aluminum alloys prepared by the prior art have uneven composition and high cost. There are a large number of shrinkage cavities and looseness defects in the titanium aluminum alloy, which seriously restricts the use and development of titanium aluminum alloys.

[0004] Therefore, how to reduce the low density of titanium aluminum alloy and improve the high temperature resistance, toughness and heat resistance of titanium aluminum alloy is a technical problem that needs to be solved urgently. Summary of the invention

[0005] The object of the present invention is to provide a high-toughness aluminum-titanium-aluminum alloy and a preparation method thereof, so as to solve one of the technical problems involved in the background technology.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] The first aspect of the present invention provides a high-toughness aluminum-titanium-aluminum alloy, comprising the following raw materials in parts by weight:

[0008] 90-93 parts of aluminum powder, 203-208 parts of titanium hydride powder, 1-5 parts of yttrium hydride powder, and 3-8 parts of modified carbon fiber; the preparation steps of the modified carbon fiber are as follows:

[0009] The aminated graphene oxide is added to an ethanol aqueous solution, subjected to ultrasonic treatment, and carbon fiber is added. The temperature is raised to 85-90° C. and stirred for reaction for 8-10 hours. The modified carbon fiber is then dried in vacuo to obtain the modified carbon fiber.

[0010] As a further embodiment of the present invention, the usage ratio of the amino-modified graphene oxide, the ethanol aqueous solution and the carbon fiber is 3.5-4.0 g:100 mL:5.0-6.5 g.

[0011] As a further embodiment of the present invention, the preparation steps of the amination graphene oxide are as follows:

[0012] The graphene oxide was added to an ethanol aqueous solution, ultrasonically dispersed, a silane coupling agent KH-550 was added, the temperature was raised to 65-70° C., reacted for 22-24 hours, and vacuum dried to obtain amino-modified graphene oxide.

[0013] As a further embodiment of the present invention, the usage ratio of graphene oxide, ethanol aqueous solution and silane coupling agent KH-550 is 3.0-5.0 g:100 mL:2.0-3.0 g.

[0014] A second aspect of the present invention provides a method for preparing a high-toughness aluminum-titanium-aluminum alloy, comprising the following steps:

[0015] Step 1, weighing each raw material by weight, mixing aluminum powder, titanium hydride powder and yttrium hydride powder to obtain a mixed powder;

[0016] Step 2, vacuum hot pressing and sintering the mixed powder obtained in step 1, and cooling to obtain an aluminum-titanium-aluminum alloy masterbatch;

[0017] Step 3, mixing the aluminum-titanium-aluminum alloy masterbatch obtained in step 2 with the modified carbon fiber, and performing vacuum suspension smelting to obtain a composite melt;

[0018] Step 4: subjecting the composite melt obtained in step 3 to investment casting and cooling to obtain a titanium-aluminum alloy.

[0019] As a further solution of the present invention, the vacuum degree of vacuum hot pressing sintering in step 2 is 2-10Pa.

[0020] As a further solution of the present invention, the sintering temperature of the vacuum hot pressing sintering in step 2 is 1340-1400° C., and the holding time is 30-90 min.

[0021] As a further solution of the present invention, the heating rate of vacuum hot pressing sintering in step 2 is 8-10°C / min.

[0022] As a further solution of the present invention, the vacuum degree of vacuum suspension smelting in step 3 is ≤0.1Pa.

[0023] As a further solution of the present invention, the smelting temperature of the vacuum suspension smelting in step 3 is 1800-2000° C., and the smelting time is 20-60 min.

[0024] Beneficial effects of the present invention:

[0025] The aluminum-titanium-aluminum alloy material prepared by using titanium hydride powder instead of pure titanium powder in the present invention reduces the oxygen content of the sample by controlling the sintering temperature, time and heating rate, thereby obtaining a fine and uniform pore structure and enhancing the mechanical properties of the alloy.

[0026] In the present invention, by introducing modified carbon fiber into the aluminum-titanium-aluminum alloy masterbatch, the added modified carbon fiber can react with the aluminum-titanium-aluminum alloy masterbatch in situ to obtain new second-phase ceramic particles. These second-phase particles can significantly refine the grain size and lamellar structure of the aluminum-titanium-aluminum alloy as heterogeneous nucleation cores. At the same time, these in-situ self-generated ceramic particles also further strengthen the titanium-titanium-aluminum alloy masterbatch, greatly improving the strength and toughness of the aluminum-titanium-aluminum alloy. In the present invention, graphene oxide is grafted on the surface of carbon fiber by chemical grafting, and the bifunctional chemical structure of silane coupling agent KH-550 is used to react with carbon fiber at one end and with graphene oxide at the other end to obtain modified carbon fiber, so that the carbon fiber has excellent dispersion performance and greatly reduces the agglomeration phenomenon. Compared with directly adding carbon fiber and graphene oxide, the modified carbon fiber has higher dispersion performance in the aluminum-titanium-aluminum alloy masterbatch, and is doped in the aluminum-titanium-aluminum alloy masterbatch to further improve the mechanical strength and toughness of the aluminum-titanium-aluminum alloy.

[0027] The preparation method of the high-toughness aluminum-titanium-aluminum alloy provided in the present invention is simple to operate, can be prepared in batches, and is easy to achieve large-scale production. At the same time, the prepared titanium-aluminum alloy has stable chemical composition, good process performance, high density, good creep resistance, high temperature strength and oxidation resistance. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] The carbon fibers used in the embodiments and comparative examples of the present invention need to be pretreated, and the pretreatment steps are as follows:

[0030] 5 g of carbon fiber was added into 100 mL of concentrated nitric acid (concentration of 65%), heated and stirred at 50° C. for 1 h, then washed with deionized water 5 times, and finally dried in a vacuum drying oven at 60° C. for 12 h to obtain carbon fiber.

[0031] Example 1

[0032] This embodiment provides a modified carbon fiber, and the preparation steps are as follows:

[0033] S1. Add 3.0 g of graphene oxide to 100 mL of ethanol aqueous solution (the volume ratio of anhydrous ethanol to water is 9:1), ultrasonically disperse for 1 h, add 2.0 g of silane coupling agent KH-550, heat to 65 ° C to react for 24 h, place in a vacuum drying oven at 60 ° C to dry for 12 h, and obtain amino-modified graphene oxide.

[0034] S2. Add 3.5 g of amino-modified graphene oxide to 100 mL of ethanol aqueous solution (the volume ratio of anhydrous ethanol to water is 9:1), ultrasonically treat, add 5.0 g of carbon fiber, heat to 85°C and stir to react for 10 h, place in a vacuum drying oven at 60°C and dry for 12 h to obtain modified carbon fiber.

[0035] Example 2

[0036] This embodiment provides a modified carbon fiber, and the preparation steps are as follows:

[0037] S1. Add 4.0 g of graphene oxide to 100 mL of ethanol aqueous solution (the volume ratio of anhydrous ethanol to water is 9:1), ultrasonically disperse for 1 h, add 2.5 g of silane coupling agent KH-550, heat to 65 ° C to react for 24 h, place in a vacuum drying oven at 60 ° C to dry for 12 h, and obtain amino-modified graphene oxide.

[0038] S2. Add 3.8 g of amino-modified graphene oxide to 100 mL of ethanol aqueous solution (the volume ratio of anhydrous ethanol to water is 9:1), ultrasonically treat, add 5.8 g of carbon fiber, heat to 85°C and stir to react for 10 hours, place in a vacuum drying oven at 60°C and dry for 12 hours to obtain modified carbon fiber.

[0039] Example 3

[0040] This embodiment provides a modified carbon fiber, and the preparation steps are as follows:

[0041] S1. Add 5.0 g of graphene oxide to 100 mL of ethanol aqueous solution (the volume ratio of anhydrous ethanol to water is 9:1), ultrasonically disperse for 1 h, add 3.0 g of silane coupling agent KH-550, heat to 65 ° C to react for 24 h, place in a vacuum drying oven at 60 ° C to dry for 12 h, and obtain amino-modified graphene oxide.

[0042] S2. Add 4.0 g of amino-modified graphene oxide into 100 mL of ethanol aqueous solution (the volume ratio of anhydrous ethanol to water is 9:1), ultrasonically treat, add 6.5 g of carbon fiber, heat to 85°C and stir to react for 10 h, place in a vacuum drying oven at 60°C and dry for 12 h to obtain modified carbon fiber.

[0043] Example 4

[0044] This embodiment provides a high-toughness aluminum-titanium-aluminum alloy and a preparation method thereof:

[0045] A high-toughness aluminum-titanium-aluminum alloy comprises the following raw materials in parts by weight:

[0046] 90 parts of aluminum powder, 203 parts of titanium hydride powder, 1 part of yttrium hydride powder, and 3 parts of modified carbon fiber in Example 1.

[0047] The preparation of the above-mentioned high toughness aluminum-titanium-aluminum alloy is as follows:

[0048] Step 1, weighing each raw material by weight, mixing aluminum powder, titanium hydride powder and yttrium hydride powder to obtain a mixed powder;

[0049] Step 2, vacuum hot pressing and sintering the mixed powder obtained in step 1, wherein the vacuum degree of vacuum hot pressing and sintering is 2 Pa, the sintering temperature is 1340° C., the holding time is 30 min, the heating rate is 8° C. / min, and cooling is performed to obtain an aluminum-titanium-aluminum alloy masterbatch;

[0050] Step 3, after mixing the aluminum-titanium-aluminum alloy masterbatch obtained in step 2 with the modified carbon fiber in Example 1, vacuum suspension melting is performed, wherein the vacuum degree is ≤0.1 Pa, the melting temperature is 1800° C., and the melting time is 20 min to obtain a composite melt;

[0051] Step 4: subjecting the composite melt obtained in step 3 to investment casting and cooling to obtain a titanium-aluminum alloy.

[0052] Example 5

[0053] This embodiment provides a high-toughness aluminum-titanium-aluminum alloy and a preparation method thereof:

[0054] A high-toughness aluminum-titanium-aluminum alloy comprises the following raw materials in parts by weight:

[0055] 90 parts of aluminum powder, 203 parts of titanium hydride powder, 1 part of yttrium hydride powder, and 3 parts of modified carbon fiber in Example 2.

[0056] The preparation of the above-mentioned high toughness aluminum-titanium-aluminum alloy is as follows:

[0057] Step 1, weighing each raw material by weight, mixing aluminum powder, titanium hydride powder and yttrium hydride powder to obtain a mixed powder;

[0058] Step 2, vacuum hot pressing and sintering the mixed powder obtained in step 1, wherein the vacuum degree of vacuum hot pressing and sintering is 2 Pa, the sintering temperature is 1340° C., the holding time is 30 min, the heating rate is 8° C. / min, and cooling is performed to obtain an aluminum-titanium-aluminum alloy masterbatch;

[0059] Step 3, after mixing the aluminum-titanium-aluminum alloy masterbatch obtained in step 2 with the modified carbon fiber in Example 2, vacuum suspension melting is performed, wherein the vacuum degree is ≤0.1 Pa, the melting temperature is 1800° C., and the melting time is 20 min to obtain a composite melt;

[0060] Step 4: subjecting the composite melt obtained in step 3 to investment casting and cooling to obtain a titanium-aluminum alloy.

[0061] Example 6

[0062] This embodiment provides a high-toughness aluminum-titanium-aluminum alloy and a preparation method thereof:

[0063] A high-toughness aluminum-titanium-aluminum alloy comprises the following raw materials in parts by weight:

[0064] 90 parts of aluminum powder, 203 parts of titanium hydride powder, 1 part of yttrium hydride powder, and 3 parts of modified carbon fiber in Example 3.

[0065] The preparation of the above-mentioned high toughness aluminum-titanium-aluminum alloy is as follows:

[0066] Step 1, weighing each raw material by weight, mixing aluminum powder, titanium hydride powder and yttrium hydride powder to obtain a mixed powder;

[0067] Step 2, vacuum hot pressing and sintering the mixed powder obtained in step 1, wherein the vacuum degree of vacuum hot pressing and sintering is 2 Pa, the sintering temperature is 1340° C., the holding time is 30 min, the heating rate is 8° C. / min, and cooling is performed to obtain an aluminum-titanium-aluminum alloy masterbatch;

[0068] Step 3, after mixing the aluminum-titanium-aluminum alloy masterbatch obtained in step 2 with the modified carbon fiber in Example 3, vacuum suspension melting is performed, wherein the vacuum degree is ≤0.1 Pa, the melting temperature is 1800° C., and the melting time is 20 min to obtain a composite melt;

[0069] Step 4: subjecting the composite melt obtained in step 3 to investment casting and cooling to obtain a titanium-aluminum alloy.

[0070] Example 7

[0071] This embodiment provides a high-toughness aluminum-titanium-aluminum alloy and a preparation method thereof:

[0072] A high-toughness aluminum-titanium-aluminum alloy comprises the following raw materials in parts by weight:

[0073] 92 parts of aluminum powder, 205 parts of titanium hydride powder, 2 parts of yttrium hydride powder, and 4 parts of modified carbon fiber in Example 1.

[0074] The preparation of the above-mentioned high toughness aluminum-titanium-aluminum alloy is as follows:

[0075] Step 1, weighing each raw material by weight, mixing aluminum powder, titanium hydride powder and yttrium hydride powder to obtain a mixed powder;

[0076] Step 2, vacuum hot pressing and sintering the mixed powder obtained in step 1, wherein the vacuum degree of vacuum hot pressing and sintering is 2 Pa, the sintering temperature is 1340° C., the holding time is 30 min, the heating rate is 8° C. / min, and cooling is performed to obtain an aluminum-titanium-aluminum alloy masterbatch;

[0077] Step 3, after mixing the aluminum-titanium-aluminum alloy masterbatch obtained in step 2 with the modified carbon fiber in Example 1, vacuum suspension melting is performed, wherein the vacuum degree is ≤0.1 Pa, the melting temperature is 1800° C., and the melting time is 20 min to obtain a composite melt;

[0078] Step 4: subjecting the composite melt obtained in step 3 to investment casting and cooling to obtain a titanium-aluminum alloy.

[0079] Example 8

[0080] This embodiment provides a high-toughness aluminum-titanium-aluminum alloy and a preparation method thereof:

[0081] A high-toughness aluminum-titanium-aluminum alloy comprises the following raw materials in parts by weight:

[0082] 93 parts of aluminum powder, 208 parts of titanium hydride powder, 4.5 parts of yttrium hydride powder, and 7 parts of modified carbon fiber in Example 1.

[0083] The preparation of the above-mentioned high toughness aluminum-titanium-aluminum alloy is as follows:

[0084] Step 1, weighing each raw material by weight, mixing aluminum powder, titanium hydride powder and yttrium hydride powder to obtain a mixed powder;

[0085] Step 2, vacuum hot pressing and sintering the mixed powder obtained in step 1, wherein the vacuum degree of vacuum hot pressing and sintering is 2 Pa, the sintering temperature is 1340° C., the holding time is 30 min, the heating rate is 8° C. / min, and cooling is performed to obtain an aluminum-titanium-aluminum alloy masterbatch;

[0086] Step 3, after mixing the aluminum-titanium-aluminum alloy masterbatch obtained in step 2 with the modified carbon fiber in Example 1, vacuum suspension melting is performed, wherein the vacuum degree is ≤0.1 Pa, the melting temperature is 1800° C., and the melting time is 20 min to obtain a composite melt;

[0087] Step 4: subjecting the composite melt obtained in step 3 to investment casting and cooling to obtain a titanium-aluminum alloy.

[0088] Example 9

[0089] This embodiment provides a high-toughness aluminum-titanium-aluminum alloy and a preparation method thereof:

[0090] A high-toughness aluminum-titanium-aluminum alloy comprises the following raw materials in parts by weight:

[0091] 90 parts of aluminum powder, 203 parts of titanium hydride powder, 1 part of yttrium hydride powder, and 3 parts of modified carbon fiber in Example 1.

[0092] The preparation of the above-mentioned high toughness aluminum-titanium-aluminum alloy is as follows:

[0093] Step 1, weighing each raw material by weight, mixing aluminum powder, titanium hydride powder and yttrium hydride powder to obtain a mixed powder;

[0094] Step 2, vacuum hot pressing and sintering the mixed powder obtained in step 1, wherein the vacuum degree of vacuum hot pressing and sintering is 8 Pa, the sintering temperature is 1380° C., the holding time is 60 min, the heating rate is 10° C. / min, and cooling is performed to obtain an aluminum-titanium-aluminum alloy masterbatch;

[0095] Step 3, after mixing the aluminum-titanium-aluminum alloy masterbatch obtained in step 2 with the modified carbon fiber in Example 1, vacuum suspension melting is performed, wherein the vacuum degree is ≤0.1 Pa, the melting temperature is 2000° C., and the melting time is 25 min to obtain a composite melt;

[0096] Step 4: subjecting the composite melt obtained in step 3 to investment casting and cooling to obtain a titanium-aluminum alloy.

[0097] Comparative Example 1

[0098] This comparative example provides a high-toughness aluminum-titanium-aluminum alloy and a preparation method thereof. Compared with Example 4, the only difference is that no modified carbon fiber is added:

[0099] A high-toughness aluminum-titanium-aluminum alloy comprises the following raw materials in parts by weight:

[0100] 90 parts of aluminum powder, 203 parts of titanium hydride powder, and 1 part of yttrium hydride powder.

[0101] The preparation of the above-mentioned high toughness aluminum-titanium-aluminum alloy is as follows:

[0102] Step 1, weighing each raw material by weight, mixing aluminum powder, titanium hydride powder and yttrium hydride powder to obtain a mixed powder;

[0103] Step 2, vacuum hot pressing and sintering the mixed powder obtained in step 1, wherein the vacuum degree of vacuum hot pressing and sintering is 2 Pa, the sintering temperature is 1340° C., the holding time is 30 min, the heating rate is 8° C. / min, and cooling is performed to obtain an aluminum-titanium-aluminum alloy masterbatch;

[0104] Step 3, the aluminum-titanium-aluminum alloy masterbatch obtained in step 2 is subjected to vacuum suspension melting, wherein the vacuum degree is ≤0.1 Pa, the melting temperature is 1800° C., and the melting time is 20 min to obtain a composite melt;

[0105] Step 4: subjecting the composite melt obtained in step 3 to investment casting and cooling to obtain a titanium-aluminum alloy.

[0106] Comparative Example 2

[0107] This comparative example provides a high-toughness aluminum-titanium-aluminum alloy and a preparation method thereof. Compared with Example 4, the only difference is that 3 parts of the modified carbon fiber in Example 1 are replaced by 3 parts of carbon fiber:

[0108] A high-toughness aluminum-titanium-aluminum alloy comprises the following raw materials in parts by weight:

[0109] 90 parts of aluminum powder, 203 parts of titanium hydride powder, 1 part of yttrium hydride powder, and 3 parts of carbon fiber.

[0110] The preparation of the above-mentioned high toughness aluminum-titanium-aluminum alloy is as follows:

[0111] Step 1, weighing each raw material by weight, mixing aluminum powder, titanium hydride powder and yttrium hydride powder to obtain a mixed powder;

[0112] Step 2, vacuum hot pressing and sintering the mixed powder obtained in step 1, wherein the vacuum degree of vacuum hot pressing and sintering is 2 Pa, the sintering temperature is 1340° C., the holding time is 30 min, the heating rate is 8° C. / min, and cooling is performed to obtain an aluminum-titanium-aluminum alloy masterbatch;

[0113] Step 3, after mixing the aluminum-titanium-aluminum alloy masterbatch obtained in step 2 with the carbon fiber, vacuum suspension melting is performed, wherein the vacuum degree is ≤0.1 Pa, the melting temperature is 1800° C., and the melting time is 20 min to obtain a composite melt;

[0114] Step 4: subjecting the composite melt obtained in step 3 to investment casting and cooling to obtain a titanium-aluminum alloy.

[0115] Comparative Example 3

[0116] This comparative example provides a high-toughness aluminum-titanium-aluminum alloy and a preparation method thereof. Compared with Example 4, the only difference is that 3 parts of the modified carbon fiber in Example 1 are replaced with 3 parts of graphene oxide:

[0117] A high-toughness aluminum-titanium-aluminum alloy comprises the following raw materials in parts by weight:

[0118] 90 parts of aluminum powder, 203 parts of titanium hydride powder, 1 part of yttrium hydride powder, and 3 parts of graphene oxide.

[0119] The preparation of the above-mentioned high toughness aluminum-titanium-aluminum alloy is as follows:

[0120] Step 1, weighing each raw material by weight, mixing aluminum powder, titanium hydride powder and yttrium hydride powder to obtain a mixed powder;

[0121] Step 2, vacuum hot pressing and sintering the mixed powder obtained in step 1, wherein the vacuum degree of vacuum hot pressing and sintering is 2 Pa, the sintering temperature is 1340° C., the holding time is 30 min, the heating rate is 8° C. / min, and cooling is performed to obtain an aluminum-titanium-aluminum alloy masterbatch;

[0122] Step 3, after mixing the aluminum-titanium-aluminum alloy masterbatch obtained in step 2 with graphene oxide, vacuum suspension melting is performed, wherein the vacuum degree is ≤0.1 Pa, the melting temperature is 1800° C., and the melting time is 20 min to obtain a composite melt;

[0123] Step 4: subjecting the composite melt obtained in step 3 to investment casting and cooling to obtain a titanium-aluminum alloy.

[0124] Comparative Example 4

[0125] This comparative example provides a high-toughness aluminum-titanium-aluminum alloy and a preparation method thereof. Compared with Example 4, the only difference is that the amount of raw materials used is different:

[0126] A high-toughness aluminum-titanium-aluminum alloy comprises the following raw materials in parts by weight:

[0127] 80 parts of aluminum powder, 203 parts of titanium hydride powder, 0.5 parts of yttrium hydride powder, and 3 parts of modified carbon fiber in Example 1.

[0128] The preparation of the above-mentioned high toughness aluminum-titanium-aluminum alloy is as follows:

[0129] Step 1, weighing each raw material by weight, mixing aluminum powder, titanium hydride powder and yttrium hydride powder to obtain a mixed powder;

[0130] Step 2, vacuum hot pressing and sintering the mixed powder obtained in step 1, wherein the vacuum degree of vacuum hot pressing and sintering is 2 Pa, the sintering temperature is 1340° C., the holding time is 30 min, the heating rate is 8° C. / min, and cooling is performed to obtain an aluminum-titanium-aluminum alloy masterbatch;

[0131] Step 3, after mixing the aluminum-titanium-aluminum alloy masterbatch obtained in step 2 with the modified carbon fiber in Example 1, vacuum suspension melting is performed, wherein the vacuum degree is ≤0.1 Pa, the melting temperature is 1800° C., and the melting time is 20 min to obtain a composite melt;

[0132] Step 4: subjecting the composite melt obtained in step 3 to investment casting and cooling to obtain a titanium-aluminum alloy.

[0133] Comparative Example 5

[0134] This comparative example provides a high-toughness aluminum-titanium-aluminum alloy and a preparation method thereof. Compared with Example 4, the only difference is that the preparation steps are different:

[0135] A high-toughness aluminum-titanium-aluminum alloy comprises the following raw materials in parts by weight:

[0136] 90 parts of aluminum powder, 203 parts of titanium hydride powder, 1 part of yttrium hydride powder, and 3 parts of modified carbon fiber in Example 1.

[0137] The preparation of the above-mentioned high toughness aluminum-titanium-aluminum alloy is as follows:

[0138] Step 1, weighing each raw material by weight, mixing aluminum powder, titanium hydride powder and yttrium hydride powder to obtain a mixed powder;

[0139] Step 2, vacuum hot pressing and sintering the mixed powder obtained in step 1, wherein the vacuum degree of vacuum hot pressing and sintering is 2 Pa, the sintering temperature is 1240° C., the holding time is 30 min, the heating rate is 5° C. / min, and cooling is performed to obtain an aluminum-titanium-aluminum alloy masterbatch;

[0140] Step 3, after mixing the aluminum-titanium-aluminum alloy masterbatch obtained in step 2 with the modified carbon fiber in Example 1, vacuum suspension melting is performed, wherein the vacuum degree is ≤0.1 Pa, the melting temperature is 1800° C., and the melting time is 20 min to obtain a composite melt;

[0141] Step 4: subjecting the composite melt obtained in step 3 to investment casting and cooling to obtain a titanium-aluminum alloy.

[0142] Comparative Example 6

[0143] This comparative example provides a high-toughness aluminum-titanium-aluminum alloy and a preparation method thereof. Compared with Example 4, the only difference is that the preparation steps are different:

[0144] A high-toughness aluminum-titanium-aluminum alloy comprises the following raw materials in parts by weight:

[0145] 90 parts of aluminum powder, 203 parts of titanium hydride powder, 1 part of yttrium hydride powder, and 3 parts of modified carbon fiber in Example 1.

[0146] The preparation of the above-mentioned high toughness aluminum-titanium-aluminum alloy is as follows:

[0147] Step 1, weighing each raw material by weight, mixing aluminum powder, titanium hydride powder and yttrium hydride powder to obtain a mixed powder;

[0148] Step 2, vacuum hot pressing and sintering the mixed powder obtained in step 1, wherein the vacuum degree of vacuum hot pressing and sintering is 2 Pa, the sintering temperature is 1340° C., the holding time is 30 min, the heating rate is 8° C. / min, and cooling is performed to obtain an aluminum-titanium-aluminum alloy masterbatch;

[0149] Step 3, after mixing the aluminum-titanium-aluminum alloy masterbatch obtained in step 2 with the modified carbon fiber in Example 1, vacuum suspension melting is performed, wherein the vacuum degree is ≤0.1 Pa, the melting temperature is 1700° C., and the melting time is 15 min to obtain a composite melt;

[0150] Step 4: subjecting the composite melt obtained in step 3 to investment casting and cooling to obtain a titanium-aluminum alloy.

[0151] The aluminum-titanium-aluminum alloys obtained in Examples 4 to 9 and Comparative Examples 1 to 5 were subjected to the following performance tests: Mechanical properties: Mechanical properties were tested according to GB / T 2298-2002; Thermal conductivity: Thermal conductivity was tested according to GB / T 3561-2008; Density: Density was tested according to the Archimedes drainage method. The above test results are shown in Table 1:

[0152] Table 1

[0153]

[0154]

[0155] It can be seen from the data in Table 1 that the compressive strength, thermal conductivity and density of the aluminum-titanium-aluminum alloys obtained in Examples 4-9 are better than those in Comparative Examples 1-6. It can be seen that the aluminum-titanium-aluminum alloy provided in the present invention has excellent strength, toughness and thermal conductivity, as well as high density, and the preparation method is simple, and can be prepared in batches, and large-scale production can be easily realized.

[0156] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0157] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A high-toughness aluminum-titanium-aluminum alloy, characterized in that: It includes the following raw materials in parts by weight: 90-93 parts of aluminum powder, 203-208 parts of titanium hydride powder, 1-5 parts of yttrium hydride powder, and 3-8 parts of modified carbon fiber; the preparation steps of the modified carbon fiber are as follows: The aminated graphene oxide is added to an ethanol aqueous solution, subjected to ultrasonic treatment, and carbon fiber is added. The temperature is raised to 85-90° C. and stirred for reaction for 8-10 hours. The modified carbon fiber is then dried in vacuo to obtain the modified carbon fiber.

2. A high toughness aluminum-titanium-aluminum alloy according to claim 1, characterized in that: The usage ratio of the amino-modified graphene oxide, the ethanol aqueous solution and the carbon fiber is 3.5-4.0 g:100 mL:5.0-6.5 g.

3. The high toughness aluminum-titanium-aluminum alloy according to claim 1, characterized in that: The preparation steps of amination graphene oxide are as follows: The graphene oxide was added to an ethanol aqueous solution, ultrasonically dispersed, a silane coupling agent KH-550 was added, the temperature was raised to 65-70° C., reacted for 22-24 hours, and vacuum dried to obtain amino-modified graphene oxide.

4. A high toughness aluminum-titanium-aluminum alloy according to claim 3, characterized in that: The usage ratio of graphene oxide, ethanol aqueous solution and silane coupling agent KH-550 is 3.0-5.0 g:100 mL:2.0-3.0 g.

5. The method for preparing a high-toughness aluminum-titanium-aluminum alloy according to claim 1, characterized in that: The following steps are involved: Step 1, weighing each raw material by weight, mixing aluminum powder, titanium hydride powder and yttrium hydride powder to obtain a mixed powder; Step 2, vacuum hot pressing and sintering the mixed powder obtained in step 1, and cooling to obtain an aluminum-titanium-aluminum alloy masterbatch; Step 3, mixing the aluminum-titanium-aluminum alloy masterbatch obtained in step 2 with the modified carbon fiber, and performing vacuum suspension smelting to obtain a composite melt; Step 4: subjecting the composite melt obtained in step 3 to investment casting and cooling to obtain a titanium-aluminum alloy.

6. The method for preparing a high-toughness aluminum-titanium-aluminum alloy according to claim 5, characterized in that: The vacuum degree of vacuum hot pressing sintering in step 2 is 2-10Pa.

7. The method for preparing a high-toughness aluminum-titanium-aluminum alloy according to claim 5, characterized in that: The sintering temperature of vacuum hot pressing sintering in step 2 is 1340-1400° C., and the holding time is 30-90 min.

8. The method for preparing a high-toughness aluminum-titanium-aluminum alloy according to claim 5, characterized in that: The heating rate of vacuum hot pressing sintering in step 2 is 8-10°C / min.

9. The method for preparing a high-toughness aluminum-titanium-aluminum alloy according to claim 5, characterized in that: The vacuum degree of vacuum suspension smelting in step 3 is ≤0.1Pa.

10. The method for preparing a high-toughness aluminum-titanium-aluminum alloy according to claim 5, characterized in that: The smelting temperature of the vacuum suspension smelting in step 3 is 1800-2000° C., and the smelting time is 20-60 min.